Effect of Biochar and Various Organic Fertilizer Combinations on Growth, Yield of Mustard Green (Brassica juncea L.), and Soil Chemical Properties of Inceptisol - Alfitriani, Pipi; Mulyati, Mulyati; Jaya, Dori Kusuma (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Mustard green (Brassica juncea L.) is one of the important leafy vegetables cultivated in tropical regions, yet its productivity is often constrained by the low fertility of Inceptisol soils. The application of organic amendments such as biochar and various animal manures has been widely reported to improve soil fertility and plant performance. Therefore, this study aimed to evaluate the effect of biochar combined with different types and dosages of organic fertilizers on the growth, yield of mustard green (Brassica juncea L.), and the chemical properties of Inceptisol soil. The experiment was conducted using a Completely Randomized Design (CRD) with seven treatments and three replications, resulting in 21 pots. The results showed that K4 (biochar 10 t ha⁻¹ + swallow manure 20 t ha⁻¹ + NPK 150 kg ha⁻¹) achieved the best growth and yield of mustard green by significantly increasing plant height, number of leaves, leaf area, fresh and dry biomass, as well as improving soil chemical properties such as pH, organic C, total N, available P, and available K. In conclusion, combination of biochar and organic fertilizers, especially with swallow manure, proved effective to enhance the soil fertility of Inceptisol for supporting growth and yield of mustard green. Based on the results, further research should be conducted using different dosages of swallow manure to obtain the optimal growth of mustard green or other vegetables in relation to reducing the use of inorganic fertilizers.